Impacts of COVID-19 on Communities in the Philippines : Results from the Philippines High Frequency Social Monitoring of COVID-19 Impacts Round 2, April 8-14, 2021 - World Bank (World Bank, Washington, DC, 2021)
The brief outlines the finding from the second round of a high frequency social monitoring survey that aimed to assess the impact of COVID 19 (coronavirus) pandemic on the poorest and most vulnerable rural communities. The survey also aimed to determine the level of understanding and source of information of the communities pertaining to the COVID 19 vaccine. The second round of phone-in survey was conducted April 4-13, 2021 and across National Community Driven Development Project (NCDDP, implemented by community DSWD) communities in nine regions in Luzon, the Visayas and Mindanao. Some of the views and observations from the respondents included : Communities were markedly concerned about vaccine safety and effectiveness and looked to doctors and health practitioners for information about vaccination plans. Getting vaccinated would likely be difficult for seniors, persons with comorbidities, and children because of health reasons. Communities preferred food, cash, and livelihood assistance.